Age‐associated reduction of cellular spreading/mechanical force up‐regulates matrix metalloproteinase‐1 expression and collagen fibril fragmentation via c‐Jun/AP‐1 in human dermal fibroblasts. Issue 6 (9th September 2014) - Qin, Zhaoping; Voorhees, John J.; Fisher, Gary J.; Quan, Taihao
Summary The dermal compartment of human skin is largely composed of dense collagen‐rich fibrils, which provide structural and mechanical support. Skin dermal fibroblasts, the major collagen‐producing cells, are interact with collagen fibrils to maintain cell spreading and mechanical force for function. A characteristic feature of aged human skin is fragmentation of collagen fibrils, which is initiated by matrix metalloproteinase 1 (MMP‐1). Fragmentation impairs fibroblast attachment and thereby reduces spreading. Here, we investigated the relationship among fibroblast spreading, mechanical force, MMP‐1 expression, and collagen fibril fragmentation. Reduced fibroblast spreading due to cytoskeletal disruption was associated with reduced cellular mechanical force, as determined by atomic force microscopy. These reductions substantially induced MMP‐1 expression, which led to collagen fibril fragmentation and disorganization in three‐dimensional collagen lattices. Constraining fibroblast size by culturing on slides coated with collagen micropatterns also significantly induced MMP‐1 expression. Reduced spreading/mechanical force induced transcription factor c‐Jun and its binding to a canonical AP‐1 binding site in the MMP‐1 proximal promoter. Blocking c‐Jun function with dominant negative mutant c‐Jun significantly reduced induction of MMP‐1 expression in response to reduced spreading/mechanical force. Furthermore, restoration of fibroblast spreading/mechanical force led to decline of c‐Jun and MMP‐1 levels and eliminated collagen fibril fragmentation and disorganization. These data reveal a novel mechanism by which alteration of fibroblast shape/mechanical force regulates c‐Jun/AP‐1‐dependent expression of MMP‐1 and consequent collagen fibril fragmentation. This mechanism provides a foundation for understanding the cellular and molecular basis of age‐related collagen fragmentation in human skin.